Kompetencja tekstotwórcza w języku odziedziczonym, czyli o kreacji i zabawie w procesie tworzenia tekstów - Bernadeta Niesporek-Szamburska (Postscriptum Polonistyczne)
The article author presents the methods of developing text-creating competence of students in a Polish diaspora. The article begins with a short presentation of discourse specificity in Polish diaspora teaching. The author also defines such notions as text competence and text-creating competence and explains their specific position in teaching bilingual students for whom Polish is an inherited language. The author refers to Cumming’s theory of two levels of language competence. Next, she discusses creativity and games as important elements supporting education and developing text-creating skills. The article concludes with several examples of exercises for students.